3D Carbon−Metal Oxide Composite Electrodes on Graphite‐Coated Stainless Steel Substrate as a High‐Performance Anode for Lithium‐Ion Batteries. Issue 12 (7th December 2021) - Mamidi, Suresh; Potphode, Darshna; Pathak, Anil D.; Sharma, Chandra S.
Abstract : 3D Carbon Microelectrodes In article number 2100102, Suresh Mamidi and co‐workers fabricate 3D carbon–metal oxide composite electrodes on graphite‐coated substrate and evaluate its electrochemical performance as an anode in lithium‐ion batteries. Here, 3D microelectrodes shorten the Li+ ions' diffusion paths. Graphite coating at the base provides efficient electron‐conducting pathways whereas cobalt oxide nanopetals improve the storage capability.